2018
DOI: 10.1007/s10661-018-6668-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ultramafic outcrops in Peninsular Malaysia and Sabah on soil and water quality

Abstract: This study focused on the influence of ultramafic terrains on soil and surface water environmental chemistry in Peninsular Malaysia and in the State of Sabah also in Malaysia. The sampling included 27 soils from four isolated outcrops at Cheroh, Bentong, Bukit Rokan, and Petasih from Peninsular Malaysia and sites near Ranau in Sabah. Water samples were also collected from rivers and subsurface waters interacting with the ultramafic bodies in these study sites. Physico-chemical parameters (including pH, EC, CEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
3
10
0
Order By: Relevance
“…Although serpentine soils are high in concentrations of Cr, Ni and Co, low concentrations of these elements have been found in the surface waters of several serpentine soils; most of the Ni (> 95%) was bound in the lattice of serpentine minerals in the residual fraction of a sequential extraction procedure [ 3 ]. While surface waters may not contain elevated levels of Cr and Ni, subsurface water can become enriched with these elements and exceed international water quality standards [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although serpentine soils are high in concentrations of Cr, Ni and Co, low concentrations of these elements have been found in the surface waters of several serpentine soils; most of the Ni (> 95%) was bound in the lattice of serpentine minerals in the residual fraction of a sequential extraction procedure [ 3 ]. While surface waters may not contain elevated levels of Cr and Ni, subsurface water can become enriched with these elements and exceed international water quality standards [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the upper range, mafic and ultramafic parent rocks gave rise to the high Fe and Mg soil (Anda, 2012;Fu et al 2012). Excessive Fe-bearing minerals released from weathered parent material in the tropical region lead to the formation and accumulation of low activity clay in the form of cambic (Van der Ent et al 2016), kandic (Tufaila et al 2011), or oxic horizon (Tashakor et al 2018;Becquer et al 2001). Meanwhile, soil containing high Ca developed from marine calcareous material such as limestone and marl (Sağlam & Dengiz, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The water analysed from hill creeks and streams of such soils showed high Mg content of 29.10 ppm, which is almost eight times more than that of the water used for irrigation in the nursery of the present study at 3.70 ppm. Tashakor et al (2018) had also reported high Mg contents in the tributaries of ultrabasic soils, ranging from 85 to 135 ppm. The water flowing through the weathering rocks of ultrabasic igneous parent material has high Mg content and that could be another reason for high Mg in the oil palm leaf 17.…”
Section: Discussionmentioning
confidence: 99%